Sosialisasi Pemanfaatan Pupuk Organik Campuran Limbah Cangkang Telur Ayam Dan Rendaman Kulit Bawang Merah Terhadap Pertumbuhan Tanaman Cabe (Capsicum Annum L.) Di Desa Sawah, Air Tiris, Kampar - Anna Dhora; Niken Ellani Patitis; Razita Hariani; Ardiansyah Hamid; Sri Wahyuni (Politeknik Kampar, 2023)
Sawah Village is one of the villages in North Kampar District, Kampar Regency, Riau. Most of the village community's occupations are farmers and housewives. Based on the results of interviews, there is household waste that is wasted and there is a lack of knowledge about the use of household waste. Therefore, there is a need for information through guidance in training for the community regarding the use of waste in their environment. This service activity aims to guide and train the community in utilizing household waste, especially egg shells and shallot skins. This activity hopes that the community will be able to make organic fertilizer independently by utilizing household waste in the form of egg shells and onion skins and can be applied to plants cultivated at home. Apart from that, organic fertilizer increases innovation, creativity and economic value for the community, especially representatives of PKK women from Sawah Village, Air Tiris, Kampar.